Children Conceived by Assisted Reproductive Technology Prone to Low Birth Weight, Preterm Birth, and Birth Defects: A Cohort Review of More Than 50,000 Live Births During 2011–2017 in Taiwan - Chang, Heng-Yu; Hwu, Wuh-Liang; Chen, Ching-Hui; Hou, Chun-Yin; Cheng, Wei (Frontiers in Pediatrics, 2020)
OBJECTIVES: The use of assisted reproductive technology (ART) has increased rapidly in Taiwan. The purpose of this study is to discuss the risks of low birth weight, preterm birth, and birth defect for children conceived by assisted reproductive technology in Taiwan. METHODS: Both National ART report database and National birth reports were obtained from the Health Promotion Administration in the Ministry of Health and Welfare in Taiwan. The cohort included live births (n = 1,405,625) and children conceived by ART (n=50,988/ 172,818 cycles) from 2011 to 2017. The prevalence of low birth weight, preterm birth, and birth defect were compared between the ART and natural pregnancy groups. RESULTS: Children conceived by ART displayed a higher rate of low birth weight as compared to those in the natural pregnancy group (p<0.001), even when analyses were restricted to singleton births (p<0.001). A higher rate of preterm birth (p<0.001) was also observed in children conceived by ART even when analyses were restricted to singleton births (p<0.05). A significant increased rate of birth defects was noted from children conceived by ART (p<0.05). CONCLUSIONS: With the increasing need for and use of ART-conceptions, the likelihood of risks induced or related to Assistant Reproductive Technology (ART) has drawn considerable attention in recent years. Taiwan, as one the leading countries with outstanding ART performances and modern medical care, the result of the current study suggests that further consideration and tighter regulations and policy are needed with regard to the use of ART.